Analisis Kerusakan Finishing Dinding Bangunan pada Lingkungan Lembap - Moch. Shofa; Hasti Suprihatin; Dandi Robi Hamzah; Yogi Aji Pramudya (Jurnal Karajata Engineering, 2026)
The finishing of walls significantly influences the visual appeal and longevity of the building structures especially in high-humidity regions. Moisture accumulation, poor material choice and improper construction practices can accelerate deterioration, leading to mold growth, discoloration, and paint peeling. This study aimed to identify the causes wall finishing damage and to determine the most effective both repair methods for enhancing durability in humid conditions. This study used a case study methodology involving the direct observation of residential building exhibiting wall damage. The findings reveal that high humidity and improper moisture transport within the wall material, is the main cause of wall damage, leading to mold development and weakening of the plaster layer, which in turn causes paint to peel. A comparison of the repair methods indicated that a denser mortar mix with a ratio of 1:1, combined with a waterproof primer and finishing paint, proved more optimal, effectively mitigating moisture effects and preventing recurring damage. To conclude, effective wall repair requires proper substrate preparation, suitable material selection, and moisture management. These insights offer practical advice for enhancing the wall finishing performance in humid areas.